An osteological documentation of hybrid wildebeest and its bearing on black wildebeest (Connochaetes Gnou) evolution - De Klerk, Bonita (My University, 2008)
ABSTRACT Wildebeest are part of the sub family Alcelaphinae and the genus Connochaetes. There are two extant species of wildebeest namely Connochaetes gnou (black wildebeest) and Connochaetes taurinus (blue wildebeest). From fossil evidence, it is thought that co-generic blue and black wildebeest diverged ca. 1Ma. Historically, geographic ranges of these two species have overlapped, but different social behaviour and habitat preference prevented sexual interaction. It has been proposed that reproductive isolation between C. taurinus and C. gnou may have disappeared due to artificial management. This has caused mate choice to change in the absence of species-specific mates, resulting in hybridisation. Most documented cases of hybridisation have occurred from dispersing blue wildebeest bulls introgressing into black herds however, the opposite has been observed. Genetic studies on a population where the blue males have introgressed with black females, show that the blue wildebeest populations are “pure” and that the black wildebeest populations are receiving an influx of blue alleles. In this research, 14 skeletons of modern hybrid Connochaetes taurinus and Connochaetes gnou, from more than one post-hybridisation generation from the Spioenkop reserve, were morphologically as well as metrically compared with a sample of ten modern “pure” blue and 15 black wildebeest. This project showed that univariate, bivariate statistical analyses of selected measurements of the skeletons were successful in identifying all of the Spioenkop individuals as hybrids. Morphologically, the hybrids exhibit a general increase in body size, and have unusual horns. The auditory bullae of the Spioenkop specimens are highly deformed, as are some axes. There is unusual bone growth on most of the post crania, morphological differences are observed on the distal ends of the metapodials, and the radius and ulna are fused in many specimens.
Keywords: Connochaetes gnou; hybridization; osteology